PENCIPTAAN MEDIA PROMOSI PURA MANGKUNEGARAN SOLO SEBAGAI UPAYA MENINGKATKAN MINAT KUNJUNGAN WISATAWAN MANCANEGARA - Harmanda, Brian; Fianto, Achmad Yanu Alif; Budiardjo, Hardman (Jurnal Art Nouveau, 2015)
Abstract: The purpose of creation of a media campaign Solo Mangkunegaran this is to preserve local cultural heritage. The study was conducted using qualitative research method is by conducting interviews, observation, documentation, and literature to obtain the data used to support conception. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that will be used to reach the intended target audience. After analyzing the data, found a concept or keyword of "The majesty of noble". Description of the concept of "the majesty of noble" is a grandeur of the noble values in Mangkunegaran. In this case how to maintain local cultural heritage that is Mangkunegaran Solo to be able to be promoted with the right strategy to the target audience. Results of the creation of the media campaign is expected to augment tourist arrivals in Mangkunegaran SoloÂ Keywords: Design, Branding,Promotion Media, Pura Mangkunegaran Solo